STUDI KINETIKA ADSORPSI LARUTAN ION LOGAM KROMIUM (Cr) MENGGUNAKAN ARANG BATANG PISANG (Musa paradisiaca) - Widihati, Ida Ayu Gede; Adhi Suastuti, Ni G. A. M. Dwi; Yohanita Nirmalasari, M. A. (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 1 Januari 2012)
Adsorption kinetics of chromium (Cr) ion on char from banana stem has been studied. The char used in this research as obtained by pyrolisys at 4000C for 0,5 hours. The parameters studied included the surface area, which was determined by spectrophotometer UV-VIS using methylen blue method, equilibrium time, the adsorption isotherm, the adsorption capacity, the influence of pH on adsorption capacity, and the adsorption kinetics. The result showed that the surface area was 3,4559 m2/g. The adsorption capacity of banana stem (Musa paradisiaca) char on Cr6+ metal was 0,8019 mg/g, obtained at 40 minutes equilibrium time with initial concentration of Cr6+ metal (adsorption isotherm) of 75 ppm. At pH 4,00, it was obtained that the maximum adsorption capacity of the adsorbent on Cr6+ metal was 0,9088 mg/g. The adsorption followed a second-order kinetics with a rate constant of 0,0008 minute-1ppm-1
Keywords: Kinetics study, banana stem (Musa paradisiaca), adsorption, chromium metal ion.